Undescribed phenylethyl flavones isolated from Patrinia villosa show cytoprotective properties via the modulation of the mir-144-3p/Nrf2 pathway. (September 2018) - Feng, Yuan; Li, Ning; Ma, Hongmei; Bei, Bei; Han, Yueqing; Chen, Gang
Abstract: Five previously undescribed phenylethyl flavones, together with six known flavones, were isolated from the whole plant of Patrinia villosa . It is the first report of natural flavones bearing phenylethyl groups. Their structures were elucidated by the interpretation of 1D and 2D NMR data. The absolute configurations of the previously undescribed phenylethyl flavones were deduced by analysis of the ECD data. All isolates were investigated for their cytoprotective effects against hydrogen peroxide (H2 O2 )-induced oxidative damage in Caco2 cells for the first time. Moreover, the mRNA expression levels of heme oxygenase-1 (HO-1) and NAD(P)H:quinine oxidoreductase 1 (NQO1), and the expression for mir-144-3p/Nrf2 pathway in Caco2 cells were examined by RT-qPCR analysis. As a result, compound5 showed most potent cytoprotective activity via modulating mir-144-3p/Nrf2 pathway and thereby scavenging of intracellular ROS in vitro . Graphical abstract: Highlights: Five undescribed phenylethyl flavones were isolated from Patrinia villosa . It is the first report of genuine natural flavones bearing phenylethyl groups. Two of the five phenylethyl flavones showed potent cytoprotective effects. It is the first report of a natural flavonoid modulating mir-144-3p expression.